2017
DOI: 10.3847/1538-4357/aa9992
|View full text |Cite
|
Sign up to set email alerts
|

Scale Invariant Jets: From Blazars to Microquasars

Abstract: Black holes, anywhere in the stellar-mass to supermassive range, are often associated with relativistic jets. Models suggest that jet production may be a universal process common in all black hole systems regardless of their mass. Although in many cases observations support such hypotheses for microquasars and Seyfert galaxies, little is known regarding whether boosted blazar jets also comply with such universal scaling laws. We use uniquely rich multi-wavelength radio light curves from the F-GAMMA program and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…1 the source was in a quiescent state for an extended period of time, has a single broadband flare and then returned to quiescence before the shock exited the core producing the 2014 event. Assuming the distance between the black hole and the radio core is 10 5 R g (Marscher et al 2008), where R g is the gravitational radius, for a 10 9.34 M ⊙ black hole (Liodakis et al 2017;Liodakis & Petropoulou 2020) the 2013-flare would occur ∼ 3 × 10 3 R g downstream from the black hole. This would place the flaring region at the edge or beyond the broad-line region (BLR) and at the acceleration and collimation zone (Marscher et al 2008(Marscher et al , 2010.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…1 the source was in a quiescent state for an extended period of time, has a single broadband flare and then returned to quiescence before the shock exited the core producing the 2014 event. Assuming the distance between the black hole and the radio core is 10 5 R g (Marscher et al 2008), where R g is the gravitational radius, for a 10 9.34 M ⊙ black hole (Liodakis et al 2017;Liodakis & Petropoulou 2020) the 2013-flare would occur ∼ 3 × 10 3 R g downstream from the black hole. This would place the flaring region at the edge or beyond the broad-line region (BLR) and at the acceleration and collimation zone (Marscher et al 2008(Marscher et al , 2010.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…There are other attempts to study the scaling laws of jetted AGN, including NLS1s [284,285], but they were not able to follow the Heinz and Sunyaev [80] relationships. Some numerical simulations have also been done, with specific reference to the jet launching from slim disks [286][287][288].…”
Section: Other Topicsmentioning
confidence: 99%
“…In Liodakis et al (2017c) we found a strong relation between the relativistic beaming-corrected broad-band radio luminosity of the jets in blazars and the mass of the central BH. Using microquasars we found that the extrapolation of the best-fit relation from blazars matches the expectations from stellar-mass BHs well, thus demonstrating that jets are scale invariant.…”
Section: Introductionmentioning
confidence: 64%
“…The viewing angle and Lorentz factor are combined to estimate the jet's Doppler factor as δ = 1/Γ(1−β cos θ). Using the BH mass and scaling relation log L(W/Hz) = (0.83 ± 0.17) × log(MBH/10 8 ) + (24.8 ± 0.15) from Liodakis et al (2017c) we estimate the jet's intrinsic monochromatic luminosity at 4.8 GHz. We have estimated the intrinsic scatter in that relation to be 0.45 dex which we take into account through random sampling.…”
Section: Population Modelmentioning
confidence: 99%